2000
DOI: 10.1111/j.1945-5100.2000.tb01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous alteration without a pronounced oxygen‐isotopic shift: Implications for the asteroidal processing of chondritic materials

Abstract: Abstract-Primitive meteorites exhibit certain features that are consistent with aqueous and thermal alteration on asteroids, but 0-isotopic analyses show only a modest heavy-isotope shift, interpreted as indicating modification in the nebula. To understand the isotopic effects of asteroidal alteration, we take the L-group ordinary chondrites weathered in Antarctica as an analogue. The data show that alteration is a two-stage process, with an initial phase producing only a negligible isotopic effect. Although s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
40
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 36 publications
8
40
1
Order By: Relevance
“…What is surprising is that significant amounts of alteration are required before any isotopic effect is observed. Bland et al (2000b) found that although these meteorites are being altered by water at a d 18 O of À 40x, there is no discernible shift in oxygen away from fall values until N25% of the iron in the meteorite has been converted to Fe 3+ (Fig. 3).…”
Section: Resultsmentioning
confidence: 93%
“…What is surprising is that significant amounts of alteration are required before any isotopic effect is observed. Bland et al (2000b) found that although these meteorites are being altered by water at a d 18 O of À 40x, there is no discernible shift in oxygen away from fall values until N25% of the iron in the meteorite has been converted to Fe 3+ (Fig. 3).…”
Section: Resultsmentioning
confidence: 93%
“…The weathering processes taking place in hot and cold deserts are markedly different (Lee and Bland 1999;Bland et al 2000) and result in distinctive shifts in the primary oxygen isotope composition of meteorite finds Clayton and Mayeda 1990;Franchi et al 1994;Bland et al 1996;Stelzner et al 1999). Weathering in the Antarctic environment will displace oxygen isotope ratios toward lighter values, while hot desert weathering will move ratios toward heavier values.…”
Section: How Useful Are Co3 Finds?mentioning
confidence: 99%
“…The respective Al/Mg ratios of the two minerals are 3,500 and 0. The absence of any 26 Mg excess even for high 27 Al/ 24 Mg ratios ( Fig. 6) demonstrates that 26 Al was not present at the time of the Al-Mg system isotopic closure.…”
mentioning
confidence: 99%
“…It was present in the early solar system at an initial abundance of 26 Al/ 27 Al Ϸ4.5 ϫ 10 Ϫ5 (19) and thus early crystallized Al-bearing minerals are expected to contain 26 Mg excesses due to 26 Al decay (37). However, no 26 Mg excesses were detected in MM40 plagioclase, providing an upper limit of the 26 Al/ 27 Al ratio at the time of isotopic closure of 2.8 ϫ 10 Ϫ8 . Assuming that 26 Al was homogeneously distributed in the early solar system and thus can serve as a relative chronometer (see ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation